2006
DOI: 10.1063/1.2397677
|View full text |Cite
|
Sign up to set email alerts
|

Liquid friction on charged surfaces: From hydrodynamic slippage to electrokinetics

Abstract: Hydrodynamic behavior at the vicinity of a confining wall is closely related to the friction properties of the liquid/solid interface. Here we consider, using Molecular Dynamics simulations, the electric contribution to friction for charged surfaces, and the induced modification of the hydrodynamic boundary condition at the confining boundary. The consequences of liquid slippage for electrokinetic phenomena, through the coupling between hydrodynamics and electrostatics within the electric double layer, are exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
229
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(246 citation statements)
references
References 38 publications
(101 reference statements)
16
229
1
Order By: Relevance
“…As it can be of order 10 or more, Joly et al propose that this effect can be at the origin of the large zeta potentials measured on hydrophobic surfaces, in spite of weak expected surface charge. 170,171 The same trend has been observed by Bouzigues et al who used evanescent waves to perform measurements of static and dynamic potentials of silanized glass, 172 and Churaev et al observed a decrease in the zeta potential on glass when a nonionic surfactant was added to the solution, which they attribute to the diminution of slip. 173 More experiments will be needed to confirm that hydrophobic surface potentials are enhanced by slip; we have to note that the usual explanation of their high potential is the occurrence of preferential adsorption of anions (OH À and Cl À ).…”
Section: Coupling With Electrokineticssupporting
confidence: 53%
See 1 more Smart Citation
“…As it can be of order 10 or more, Joly et al propose that this effect can be at the origin of the large zeta potentials measured on hydrophobic surfaces, in spite of weak expected surface charge. 170,171 The same trend has been observed by Bouzigues et al who used evanescent waves to perform measurements of static and dynamic potentials of silanized glass, 172 and Churaev et al observed a decrease in the zeta potential on glass when a nonionic surfactant was added to the solution, which they attribute to the diminution of slip. 173 More experiments will be needed to confirm that hydrophobic surface potentials are enhanced by slip; we have to note that the usual explanation of their high potential is the occurrence of preferential adsorption of anions (OH À and Cl À ).…”
Section: Coupling With Electrokineticssupporting
confidence: 53%
“…The interest of slip in such devices is to possibly lead to a much better efficiency, in relation with the enhanced streaming potentials already discussed. 171 Ren and Stein have modeled the role of slippage in streaming potential-based energy conversion: it decreases the fluidic impedance and increases the streaming conductance. 178 They show that these effects are moderated by a decrease in the electrical impedance (dissipation); a diverging slip length could lead to almost 100% efficiency (see Figure 5.22).…”
Section: Coupling With Electrokineticsmentioning
confidence: 99%
“…Bakli and Chakraborty also found evidence of salt--specific effects related to the ion hydration strength (49), and extended their investigation to electrokinetic energy conversion (80). Joly et al (81) investigated the effect of salt on slip length with charged confining walls. In that case, the slip length was mainly controlled by the surface charge, while salt concentration effects were negligible.…”
Section: Graphene -Based Membranesmentioning
confidence: 99%
“…The relation was modified for non-wetting charged surfaces by considering the fluid slip effect [65], which was experimentally validated [66]. Surface roughness is another factor that needs to be taken into consideration.…”
Section: Introductionmentioning
confidence: 99%